Cardiovascular effects associated with chimeric antigen receptor T cell therapy in cancer patients: A meta-analysis - Chen, Li-Rong; Li, Ya-Jia; Zhang, Zheng; Wang, Ping; Zhou, Tao; Qian, Kai; Fan, Yu-Xin; Guo, Yu; He, Gong-Hao; Shen, Lei (Frontiers in Oncology, 2022)
Background: Although numerous studies conﬁrmed the marked efﬁcacy of CAR-T cells in many hematologic malignancies, severe cardiovascular toxicities remain to be a major obstacle when incorporating this technology. Furthermore, previous individual investigations regarding the cardiovascular toxicities of CAR-T cell therapy also reported controversial conclusions. Therefore, a meta-analysis was performed to further evaluate the impacts of CAR-T cell therapy on cardiovascular toxicities. Methods: The PubMed, Embase, Web of Science and ClinicalTrials.gov databases were searched for eligible studies up to April 2022. All analysis was carried out using the R 4.1.0 software. Results: Eventually, 25 related studies consisting of 2059 patients were enrolled in the current meta-analysis. We discovered that pooled incidence rate of all-cause mortality rate was 14.1% and that the pooled incidence rate of over all cardiovascular (CV) events and CV events with cytokine release syndrome (CRS) grade ≥ 2 were 25.6% and 14.2%, respectively. Pooled incidence of hypotension was 28.6%. Further analysis showed that the incidence rate of arrhythmias, cardiovascular dysfunction, heart failure (HF), CV deaths, acute coronary syndrome (ACS), cardiomyopathy, cardiac arrest, and other CV events were, 19.2%, 8.0%, 5.3%, 1.8%, 2.5%, 2.9%, 1.3% and 1.9%, respectively. Conclusion: Cancer patients treated with CAR-T cell therapy were at risk for cardiovascular toxicities, of which the most common cardiovascular events were arrhythmias, cardiovascular dysfunction and heart failure. These findings would contribute to achieving more rational and individualized use of CAR-T cells in clinical treatment.